An Investigation of Thai Pre-service English Teachers’ Perceptions Towards Using English as The Medium of Instruction in Teaching Practicum - Ruengwatthakee, Pimrawee; Haas, Lory (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
This exploratory study aims to 1. investigate the perceptions of Thai pre-service English teachers towards using English as the medium of instruction in schools, 2. to explore the factors that motivate Thai pre-service teachers to speak English as the medium of instruction, and 3. to explore the challenges Thai pre-service teachers have on using English as the medium of instruction in teaching practicum. The participants were 40 students in an English as a Foreign Language (EFL) Teacher Training Program at a university in the central region of Thailand, who attended the Teaching Practicum. A mixed methods research design was employed as a data collection and analysis tool. The research instruments were an online survey with 21 questions that related to perceptions towards using English when teaching during their practicum experience and semi-structured interview. The quantitative results showed that more than half of participants agreed that using English when teaching is important, however, less than half of them strongly agreed that they tried to use English as much as they should. The qualitative results indicated that the participants avoid using English when teaching because they are concerned about their English competence including vocabulary, grammar, and pronunciation. Additionally, most of the participants perceived that using English when teaching in the classroom may cause difficulties for their students to understand, causing unwillingness to speak English. Based on the findings, the study showed there is a need to determine strategies or provide training to decrease Thai pre-service English teachers’ foreign language speaking anxiety.